2015
DOI: 10.1111/lam.12479
|View full text |Cite
|
Sign up to set email alerts
|

Delftia tsuruhatensis WGR-UOM-BT1, a novel rhizobacterium with PGPR properties from Rauwolfia serpentina (L.) Benth. ex Kurz also suppresses fungal phytopathogens by producing a new antibiotic-AMTM

Abstract: In this study, we reported that Delftia tsuruhatensis WGR-UOM-BT1 strain has the plant growth promotion activities such as rhizosphere colonization (tomato), IAA production, 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity and phosphate solubilization. This bacterial strain was found producing an antimicrobial nitrogen-containing heterocyclic compound identified as 'amino(5-(4-methoxyphenyl)-2-methyl-2-(thiophen-2-yl)-2,3-dihydrofuran-3-yl)methanol' [C17 H19 NO3 S] (AMTM), which is new to the bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 17 publications
(19 reference statements)
2
8
0
Order By: Relevance
“…Similar results related to the bacterial inhibition of fungal conidia germination and hyphal growth are very common in natural ecosystems, e.g., some bacterial species from the families of Xanthomonadaceae, Rhizobiaceae, Alcaligenaceae and Micrococcaceae can decrease fungal conidia germination and mycelial growth . In fact, some of the bacterial species that showed significant inhibitory effects on B. bassiana have been reported to produce various types of antifungal metabolites or enzymes, e.g., C. freundii shows antifungal activities against various types of fungi by producing antifungal chitinase D. tsuruhatensis can produce new antifungal antibiotics …”
Section: Discussionsupporting
confidence: 56%
“…Similar results related to the bacterial inhibition of fungal conidia germination and hyphal growth are very common in natural ecosystems, e.g., some bacterial species from the families of Xanthomonadaceae, Rhizobiaceae, Alcaligenaceae and Micrococcaceae can decrease fungal conidia germination and mycelial growth . In fact, some of the bacterial species that showed significant inhibitory effects on B. bassiana have been reported to produce various types of antifungal metabolites or enzymes, e.g., C. freundii shows antifungal activities against various types of fungi by producing antifungal chitinase D. tsuruhatensis can produce new antifungal antibiotics …”
Section: Discussionsupporting
confidence: 56%
“…This suggested that the consortium exhibited better disease control efficacy over the commercially available fungicides (78.80–79.26% for damping off and 80.32–82.65% for anthracnose), fumigation (77.35% for damping off and 81.80% for anthracnose) and soil solarization (74.56% for damping off and 84.40% for anthracnose) practices utilized for disease control. It is because of the antagonistic microbes ( Bacillus pumilus and Bacillus subtilis ) in the rhizosphere which protect the host plant by directly suppressing the growth and proliferation of phytopathogens [25,26]. Competitive root tip colonization by rhizobacterial strains might play a crucial role in the efficient control of soil-borne diseases [27].…”
Section: Resultsmentioning
confidence: 99%
“…river [ 45 ], soil [ 46 ], human gut [ 47 ] and plant ( Dendrobium aurantiacum ) [ 48 , 49 ]. In recent years, Shigella was identified as a PGPR [ 50 ], and Delftia has been found to promote plant growth through suppressing fungal phytopathogens [ 51 ], and transforming or degrading multiple organic and inorganic toxins [ 52 , 53 ]. Regardless of the fact that they are abundant bacteria in D .…”
Section: Discussionmentioning
confidence: 99%